Analisis Sosial, Ekonomi, dan Keuangan pada Bagi Hasil dan Rugi Kerjasama Islam (Studi Kasus pada Bisnis Tembakau di Kabupaten Jember, Indonesia - Novi Puspitasari; Hari Sukarno; Hikmah Wardatatul Hasanah (IQTISHODUNA: Jurnal Ekonomi Islam, 2021)
The purpose of this study are: (1) to investigate the implementation of partnerships in the VOK tobacco business in an Islamic perspective, whether include mukhabarah, muzara’ah, or musaqah contract; (2) to explore the partnership implementation of VOK tobacco business on social, economic, and finance. This study use the snowball method with in depth interview. This research captured that there are two contracts of Islamic partnership on tobacco business, namely mukhabarah and muzara'ah. The social impact is the availability of jobs for people who do not own land/rice fields, thus helping the government to reduce unemployment and create close kinship in the community. The manifestation of the economic impact is that people who do not own land can still earn income for live. This study shows that there is a difference formula in calculating the profit sharing between the net farm income (NFI) and local culture formula. The local cultural formula does not use the real cost to count the net profit which is considered injustice. It is important to note that injustice is something that is against Islamic belief. Profit-sharing ratio between landowner and land tiller is 50%: 50% of net income.